Synthesis of (Al2OC)x(AlN)1-x whiskers via Al2O(g) transient phase in Al-Al2O3 composite at 1000–1300°C in flowing N2 - Yang Sun; Yong Li; Lixin Zhang; Yinan Shen; Jialin Sun (Journal of Asian Ceramic Societies, 2020)
In this paper, (Al2OC)x(AlN)1-x whiskers are successfully synthesized in resin-bonded Al-Al2O3 composite at 1000–1300°C in flowing N2 by forming highly active AlN in the composite with Al2O(g) as a transition phase. The formation of highly active AlN reduces the formation temperature of (Al2OC)x(AlN)1-x, while the diffusion and mass transfer of Al2O(g) construct a highly active Al2O3-Al4C3-AlN ternary system in the composite, and thus make the (Al2OC)x(AlN)1-x grow into a whisker morphology. The formation mechanism of the Al2O(g) can be expressed as: The uniformly dispersed C produced by phenolic resin enlarges the reaction temperature range of Al by forming an Al2O3-AlN-Al4C3-C composite shell wrapping the Al particle, and the reaction between continuously exposed fresh liquid Al and trace O2(g) in high-purity nitrogen achieves the continuous generation of the Al2O(g).